1984
DOI: 10.1002/art.1780271202
|View full text |Cite
|
Sign up to set email alerts
|

Low C3B receptor reactivity on erythrocytes from patients with systemic lupus erythematosus detected by immune adherence hemagglutination and radioimmunoassays with monoclonal antibody

Abstract: C3b receptor (CR1) on erythrocytes from 23 patients with systemic lupus erythematosus (SLE) and 124 normal controls was determined by immune adherence hemagglutination (IAHA) and radioimmunoassay. The binding of radiolabeled monoclonal anti‐CR1 to erythrocytes and their lysate was distributed continuously in a wide range. The majority of SLE patients showed low binding by both assays. CR1 sites on erythrocytes were determined also by Scatchard plot analysis and standardized by the number of similarly determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 19 publications
5
36
0
Order By: Relevance
“…The role of genetic factors in SLE in general (54-56) and the observations of familial deficiencies of erythrocyte CRl in this study and in previous studies (1,3,5) led to an analysis of CR1 expression by B cells of the first-degree relatives of 8 patients. Although the mean expression of this receptor by cells from all re1,atives did not differ from that of cells from normal persons, those relatives having low expression of CR1 tended to cluster in families in which more than 1 member had SLE ( Figure 5).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The role of genetic factors in SLE in general (54-56) and the observations of familial deficiencies of erythrocyte CRl in this study and in previous studies (1,3,5) led to an analysis of CR1 expression by B cells of the first-degree relatives of 8 patients. Although the mean expression of this receptor by cells from all re1,atives did not differ from that of cells from normal persons, those relatives having low expression of CR1 tended to cluster in families in which more than 1 member had SLE ( Figure 5).…”
Section: Discussionsupporting
confidence: 55%
“…Three studies have shown that deficiency of erythrocyte CR1 occurs not only in patients with SLE, but also in their relatives (1,3,5). Therefore, we analyzed the CR1 and CR2 of leukocytes obtained from the members of 8 families having a lupus proband.…”
Section: Expression Of Cr1 and Cr2 By B Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…The numbers of erythrocyte CR1 in healthy individuals seem to be genetically determined (8,(19)(20)(21)(22). The origin of the reduction in numbers of CRl in patients with SLE has been the subject of discussion.…”
Section: Discussionmentioning
confidence: 99%
“…The erythrocytes (E) of many patients with SLE display a relative deficiency of complement receptor (CRl) [1][2][3][4][5][6][7][8] as well as increased deposition of the C3-split product, C3d,g, on the E-membrane [9][10][11][12]. Both inherited [3,7] and acquired [1,4,6] factors have been reported to contribute to the deficiency of E-CRl in SLE patients.…”
Section: Introductionmentioning
confidence: 99%